Pediatric palliative care for youth with HIV/AIDS: systematic review of the literature - Wilkins ML (Dove Medical Press, 2013)
Megan L Wilkins,1 Ronald H Dallas,1 Kathleen E Fanone,2 Maureen E Lyon3,4 1St Jude Children's Research Hospital, Department of Infectious Diseases, Memphis, TN, USA; 2Johns Hopkins Medical Center, Department of Pediatric Medicine, Baltimore, MD, USA; 3Children's National Medical Center, 4George Washington University School of Medicine and Health Sciences, Washington, DC, USA Abstract: Improvement in treatment has led to decreased death in youth with human immunodeficiency virus (HIV) in developed countries. Despite this, youth with HIV are still at risk for increased mortality and morbidity compared with their uninfected counterparts. In developing countries, high numbers of youth die from acquired immune deficiency syndrome (AIDS)-related illnesses due to lack of access to consistent antiretroviral treatment. As a result, pediatric palliative care is a relevant topic for those providing care to youth with HIV. A systematic review was conducted to gather information regarding the status of the literature related to pediatric palliative care and medical decision-making for youth with HIV. The relevant literature published between January 2002 and June 2012 was identified through searches conducted using PubMed, CINAHL, Scopus, and PSYCInfo databases and a series of key words. Articles were reviewed by thematic analysis using the pillars of palliative care set out by the National Consensus Project. Twenty-one articles were retained after review and are summarized by theme. In general, few empirically based studies evaluating palliative care and medical decision-making in youth with HIV were identified. Articles identified focused primarily on physical aspects of care, with less attention paid to psychological, social, ethical, and cultural aspects of care. We recommend that future research focuses on broadening the evaluation of pediatric palliative care among youth with HIV by directly evaluating the psychological, social, ethical, and cultural aspects of care and investigating the needs of all involved stakeholders. Keywords: pediatric palliative care, human immunodeficiency virus, acquired immune deficiency syndrome, advance care planning, medical decision-making